Why e- PDS? - A S DILEEP, SHANAND K P (KERALA CALLING, 2014)
e-PDS is a system in which the whole process of public distribution of essential commodities were computerized. The entire process begins from applying for ration card to final delivery of commodities to the end beneficiaries were digitalized.